2011
DOI: 10.1002/macp.201100473
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐Solid‐State Dye‐Sensitized Solar Cells Using Nanocomposite Gel Polymer Electrolytes Based on Poly(propylene carbonate)

Abstract: Poly(propylene carbonate) (PPC) is synthesized from the copolymerization of CO 2 and propylene oxide. Novel nanocomposite gel polymer electrolytes (GPEs) are prepared by utilizing PPC, organic solvents containing a redox couple, and aluminum oxide nanoparticles for application in dye-sensitized solar cells (DSSCs). The quasi-solid-state DSSC assembled with optimized nanocomposite GPEs exhibits a relatively high conversion effi ciency of 6.16% at 100 mW cm − 2 and better stability than DSSC with liquid electrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…PPC chains are an important component of GPE polymeric frameworks because they effectively solvate the ion salt and serve as a solvent gelator. [29][30][31] The cross-linking of BR not only enhances the elasticity and mechanical strength of the XBRPC polymeric framework, but also lower the production cost of the GPEs. Blending PEG with XBRPC precursors increases the compatibility of BR and PPC and forms composite lms with homogeneous structure.…”
Section: Resultsmentioning
confidence: 99%
“…PPC chains are an important component of GPE polymeric frameworks because they effectively solvate the ion salt and serve as a solvent gelator. [29][30][31] The cross-linking of BR not only enhances the elasticity and mechanical strength of the XBRPC polymeric framework, but also lower the production cost of the GPEs. Blending PEG with XBRPC precursors increases the compatibility of BR and PPC and forms composite lms with homogeneous structure.…”
Section: Resultsmentioning
confidence: 99%
“…PPC has a similar structure to carbonate-based organic solvents presently used in conventional gel electrolytes, implying that it may have good compatibility with the lithium salts used in the gel electrolytes as well as offer good interfacial contact with commonly used electrodes in electrochemical devices. Compared with PEO and P(VdF- co -HFP), PPC-based electrolytes are highly transparent due to the amorphous nature of PPC . Moreover, unlike PMMA, the T g of PPC is very close to room temperature and hence can be turned into a rubbery state by incorporation of a small amount of IL, facilitating the motion of lithium ions in the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is found that J sc and η of the QS‐DSSCs are enhanced by introducing the Fe 3 O 4 @NCs/TiCl nanocomposite. Compared with other works in which different nanofilters and polymer networks are used, the system based on the novel Fe 3 O 4 @NCs/TiCl nanocomposite and PVAc polymeric network shows the significant improvement in J sc and η …”
Section: Introductionmentioning
confidence: 80%